Dry-method binder and preparation method thereof as well as electrode plate and preparation method thereof

By using solvent-free dry binder prepared by blending maleic anhydride grafted polypropylene with metal salt, the problem of toxic solvents in traditional battery manufacturing is solved, and efficient and low-cost electrode sheet preparation is achieved, which improves the battery Performance and sustainability.

CN119505768AActive Publication Date: 2025-02-25GUANGZHOU LUSHAN NEW MATERIALS

Patent Information

Application Number
CN202510059562.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-02-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Toxic solvents used in the manufacture of traditional lithium-ion battery electrodes, such as NMP, have problems such as environmental pollution, health threats and high costs. The industrial manufacturing process of dry bonding agents also involves a large number of solvents and high temperature and high pressure conditions, resulting in bonding. The thermal and mechanical stability of the agent is insufficient.

Method used

The solvent-free dry binder is prepared by blending maleic anhydride grafted polypropylene with metal salt through a kneading process. The ion-aggregated conduction network is formed through melting treatment and kneading, thereby improving the bonding strength and conductivity.

Benefits of technology

The low-cost and efficient preparation of solvent-free dry process is achieved, which improves the load and rate performance of the electrode sheet, while reducing environmental and health risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505768A_ABST
    Figure CN119505768A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary ion batteries, in particular to a dry binder and a preparation method thereof as well as an electrode plate and a preparation method thereof. The preparation method of the dry binder comprises the following steps: mixing and granulating a graft polymer and a metal salt to obtain the dry binder, the graft polymer comprises maleic anhydride grafted polypropylene. Maleic anhydride grafted polypropylene is used as a polymer matrix and is blended with the metal salt to prepare the solvent-free dry-method binder through a mixing process, and the solvent-free dry-method binder has excellent binding strength and lithium ion conductivity, and is high in use safety and low in raw material cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of secondary ion batteries, and in particular to a dry binder and a preparation method thereof, and an electrode sheet and a preparation method thereof. Background Art

[0002] Rechargeable lithium-ion batteries (LIBs) have become an important energy storage technology, especially in the context of growing global attention to green technologies and environmental issues. Although lithium-ion batteries are widely regarded as clean energy storage devices, their manufacturing process is still not fully sustainable. A significant environmental and health issue stems from the toxic and volatile solvents used in the electrode manufacturing stage.

[0003] In traditional lithium-ion battery electrode manufacturing, the metal current collector is typically coated with a slurry consisting of an active material, a conductive agent, and a polymer binder (such as polyvinylidene fluoride, PVDF) mixed with a solvent called N-methyl-2-pyrrolidone (NMP). Although NMP is an effective solvent for PVDF, it is both expensive and toxic. NMP evaporates slowly, making the drying and recycling process time-consuming and costly. In addition, NMP is harmful to health, such as causing male infertility, and is flammable, increasing the risk of fire. Long-term exposure to NMP not only threatens workers' health, but also increases production costs and environmental impacts, so it is imperative to find safer and more sustainable alternatives in lithium battery manufacturing.

[0004] The dry process is regarded as a new manufacturing method for the next generation of lithium-ion battery electrodes because it has unparalleled advantages in operating costs and energy efficiency compared to traditional solvent processes. In addition, since no solvent is used, the dry process can increase the maximum load threshold of the active material, thereby achieving electrode manufacturing with a higher load, paving the way for the miniaturization of batteries. However, although the dry process is solvent-free, the current industrial manufacturing process of its auxiliary adhesive material involves the use of a large amount of solvents and fluorinated polymers, such as the PTFE dry adhesive and acrylate dry adhesive involved in the Chinese patent applications with publication numbers CN117777343A, CN117691110A, and CN117438531A. In addition, since the dry adhesive involves a high-temperature shear fiberization process, the adhesive is required to have excellent thermal stability and mechanical stability as well as electrolyte resistance, while the fiberization of the PTFE adhesive requires high temperature and high pressure conditions, and the acrylate adhesive has problems such as poor mechanical properties.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a dry binder and a preparation method thereof, as well as an electrode sheet and a preparation method thereof, which can prepare the binder masterbatch through a solvent-free dry process, reduce the manufacturing cost and increase the electrode sheet load.

[0007] In order to achieve the above-mentioned object of the present invention, the first aspect of the present invention provides a method for preparing a dry binder, comprising the following steps: The grafted polymer and the metal salt are mixed and granulated to obtain a dry binder; The grafted polymer includes maleic anhydride grafted polypropylene.

[0008] In a specific embodiment of the present invention, the grafted polymer includes maleic anhydride grafted polypropylene and maleic anhydride grafted polystyrene.

[0009] In a specific embodiment of the present invention, in the grafted polymer, the mass ratio of the maleic anhydride grafted polypropylene to the maleic anhydride grafted polystyrene is (80-98): (20-2).

[0010] In a specific embodiment of the present invention, in the grafted polymer, the proportion of the grafted group unit is 0.01 wt% to 5 wt%.

[0011] In a specific embodiment of the present invention, the metal salt is composed of cations and anions; the cations include Li + 、Na + , K + 、Zn 2+ 、Al 3+ Mg 2+ , Mn 2+ and Ga 2+ The anion includes any one of hydroxide, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, chloride, sulfate, carbonate, nitrate, perchlorate, tetrafluorophosphate, hexafluorophosphate, bis(oxalatoborate) and difluoro(oxalatoborate) ions. Further, the metal salt includes at least one of LiOH, LiTFSI, LiFSI, LiClO4, LiBF4, LiPF6, LiBOB, LiDFOB, NaOH, NaClO4, NaPF6 and Na2CO3.

[0012] In a specific embodiment of the present invention, the molar ratio of the grafted group unit in the grafted polymer to the cation in the metal salt is (0.1-30):1.

[0013] In a specific embodiment of the present invention, the grafted polymer is first melt-treated and then mixed with the metal salt. Further, the temperature of the melt treatment is 120-200°C, and the temperature of the mixing is 60-150°C.

[0014] The second aspect of the present invention provides a dry binder prepared by the method for preparing the dry binder of the first aspect.

[0015] The third aspect of the present invention provides an electrode sheet, which is prepared by using the dry binder prepared by the preparation method of the first aspect of the present invention or the dry binder of the second aspect.

[0016] The fourth aspect of the present invention provides a method for preparing the electrode sheet of the third aspect, comprising the following steps: (a) mixing a dry binder, an electrode active material, a conductive agent and optionally a filler in proportion, and blending by screw shearing to obtain a fiberized solid; (b) The solid material is heated and rolled into a sheet, and then hot-pressed and bonded to the surface of a current collector to obtain an electrode sheet.

[0017] In a specific embodiment of the present invention, the mass ratio of the dry binder, the electrode active material and the conductive agent is (1-10): (80-95): (5-10).

[0018] Compared with the prior art, the present invention has the following beneficial effects: The invention uses maleic anhydride grafted polypropylene as a polymer matrix and mixes it with a metal salt through a mixing process to prepare a solvent-free dry binder. On the one hand, the maleic anhydride grafted polypropylene has excellent electrolyte resistance. On the other hand, the solvent-free mixing process, the good solvation ability of the maleic anhydride group to metal ions and the unique microphase structure of the grafted side chain enable the polymer matrix to accommodate and dissociate the electrolyte salt, thereby ensuring the bonding strength of the binder and forming a conductive network of ion aggregation, significantly improving the room temperature ionic conductivity, and helping to improve the rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 Schematic diagram of a twin-screw for preparing a dry electrode sheet provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0021] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0022] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0023] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0024] The first aspect of the present invention provides a method for preparing a dry binder, comprising the following steps: The grafted polymer and the metal salt are mixed and granulated to obtain a dry binder; Grafted polymers include maleic anhydride grafted polypropylene.

[0025] In the preparation method of the present invention, a grafted polymer is selected as the main polymer of the dry binder. Compared with the existing PTFE dry fiber binder, the grafted polymer has a mature synthesis process, low cost, and excellent ion conductivity, and can be prepared in batches by a solvent-free hot-melt grafting method. In addition, the present invention uses maleic anhydride grafted polypropylene, which has good electrolyte resistance and bonding properties; the grafted maleic anhydride group can ensure stable bonding with the powder active material and the current collector, and the maleic anhydride group can also interact with the metal salt to promote ion conduction, improve performance while being compatible with the existing production line process, and has a better cost advantage.

[0026] In a specific embodiment of the present invention, the grafted polymer includes maleic anhydride grafted polypropylene and maleic anhydride grafted polystyrene. Maleic anhydride grafted polystyrene and maleic anhydride grafted polypropylene are used together to form a unique microphase structure, which can further improve the cohesive strength and room temperature ionic conductivity of the binder.

[0027] There are many types of maleic anhydride grafted polymers, such as maleic anhydride grafted polyethylene, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted ethylene-vinyl acetate copolymer, maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer, maleic anhydride grafted polyphenylene ether, maleic anhydride grafted ethylene propylene diene rubber, etc. The inventors of the present invention have found that the use of maleic anhydride grafted polypropylene and maleic anhydride grafted polystyrene can not only ensure the electrolyte resistance of the prepared adhesive, but also ensure the bonding performance and cost.

[0028] In a specific embodiment of the present invention, in the grafted polymer, the mass ratio of maleic anhydride grafted polypropylene to maleic anhydride grafted polystyrene is (80-98):(20-2), for example, it can be 80:20, 82:18, 85:15, 88:12, 90:10, 92:8, 95:5, 98:2 or a range consisting of any two of them, thereby taking into account the improvement of dry process processability, the bonding performance of the prepared dry adhesive, the cohesive strength and the room temperature ionic conductivity.

[0029] In a specific embodiment of the present invention, the weight average molecular weight of the grafted polymer is 5×10 5 ~2×10 7 Da, for example, can be 5×10 5 Da, 8×10 5 Da, 1×10 6 Da, 3×10 6 Da, 5×10 6 Da, 8×10 6 Da, 1×10 7 Da, 1.2×10 7 Da, 1.5×10 7Da, 1.8×10 7 Da, 2×10 7 Da or any two of them. Further, the weight average molecular weight of the grafted polymer is 5×10 5 ~1.5×10 7 Da.

[0030] In a specific embodiment of the present invention, in the grafted polymer, the proportion of the grafted group unit is 0.01wt% to 5wt%, for example, it can be 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 3wt%, 4wt%, 5wt% or any two thereof. Further, in the grafted polymer, the proportion of the grafted group unit is 0.1wt% to 2wt%, which helps to interact with the metal salt to promote ion conduction and improve battery performance while ensuring the bonding strength of the binder to the active material and the current collector.

[0031] The graft polymer of the present invention can be a commercial graft polymer, and the type, molecular weight, grafting rate, etc. can meet the above conditions.

[0032] In a specific embodiment of the present invention, the metal salt is composed of cations and anions; the cations include Li + 、Na + , K + 、Zn 2+ 、Al 3+ Mg 2+ , Mn 2+ and Ga 2+ Any of; anions include hydroxide (OH - ), bis(trifluoromethanesulfonyl)imide (TFSI - ), bis(fluorosulfonyl)imide (FSI - ), chloride ion (Cl - ), sulfate ion (SO4 2- ), carbonate ions (CO3 2- ), nitrate ion (NO3 - ), perchlorate ion (ClO4 - ), tetrafluorophosphate ion (BF4 - ), hexafluorophosphate ion (PF6 - ), bis(oxalatoborate) ion (BOB - ) and difluorooxalatoborate ion (DFOB -). Further, the metal salt includes at least one of LiOH, LiTFSI, LiFSI, LiClO4, LiBF4, LiPF6, LiBOB, LiDFOB, NaOH, NaClO4, NaPF6 and Na2CO3.

[0033] In a specific embodiment of the present invention, the molar ratio of the grafted group unit in the grafted polymer to the cation in the metal salt is (0.1-30) : 1, for example, it can be 0.1: 1, 0.5: 1, 1: 1, 3: 1, 5: 1, 10: 1, 15: 1, 20: 1, 25: 1, 30: 1 or a range consisting of any two of them, and further is (0.5-5) : 1. The molar ratio of the grafted group unit to the cation in the metal salt is regulated within the above range to ensure both the bonding performance and the improvement of the room temperature ionic conductivity; to avoid the degradation of the bonding performance caused by too many cations in the metal salt, and to avoid the insignificant improvement of the room temperature ionic conductivity caused by too few cations in the metal salt.

[0034] In a specific embodiment of the present invention, the grafted polymer is first melt-treated and then mixed with the metal salt. Further, the temperature of the melt treatment is 120 to 200°C, for example, 120°C, 140°C, 150°C, 180°C, 200°C or any two thereof; the mixing temperature is 60 to 150°C, for example, 60°C, 80°C, 100°C, 120°C, 140°C, 150°C or any two thereof.

[0035] In actual operation, the melting treatment and mixing process can be carried out by a twin-screw extruder. Specifically, the grafted polymer, metal salt, etc. can be dried and dehydrated first, and then the grafted polymer after drying and dehydration is added to the twin-screw extruder, set to the temperature of melting treatment, after the grafted polymer is melted, the metal salt is added to the molten grafted polymer through the feed hopper in proportion, and the mixing temperature is set, and the maleic anhydride group of the grafted polymer is caused to open the ring and complex with the metal salt to form an ionic polymer through the temperature and shear force of the screw, and then extruded through the extrusion die head and cooled, and then granulated by a granulator to obtain a dry binder.

[0036] In a specific embodiment of the present invention, the temperature for drying and removing water may be 100-140°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C or a range consisting of any two thereof.

[0037] The second aspect of the present invention provides a dry binder prepared by the method for preparing the dry binder of the first aspect.

[0038] The third aspect of the present invention provides an electrode sheet, which is prepared by using the dry binder prepared by the preparation method of the first aspect of the present invention or the dry binder of the second aspect.

[0039] The fourth aspect of the present invention provides a method for preparing the electrode sheet of the third aspect, comprising the following steps: (a) mixing a dry binder, an electrode active material, a conductive agent and optionally a filler in proportion, and blending by screw shearing to obtain a fiberized solid; (b) The solid material is heated and rolled into a sheet, and then hot-pressed and bonded to the surface of the current collector to obtain an electrode sheet.

[0040] The blending can be carried out by a screw extruder, the heating and calendering can be carried out by a roller press, and the hot pressing and laminating can be carried out by a hot roller press. Specifically, in the shear blending, the mixing can be carried out at a speed of 200 to 300 rpm for 5 to 15 minutes, and then at a speed of 300 to 400 rpm for 20 to 40 minutes.

[0041] When preparing a dry-process negative electrode sheet, the electrode active material can be a negative electrode active material; when preparing a dry-process positive electrode sheet, the electrode active material can be a positive electrode active material. The following embodiments are described using graphite, a negative electrode active material, as an example, but are not limited thereto.

[0042] Figure 1 A schematic diagram of a twin-screw extruder for preparing a dry electrode sheet provided in an embodiment of the present invention. A dry binder, electrode active material, conductive agent, etc. can be added to a twin-screw extruder through different feeding hoppers to obtain a fiberized solid. The solid is then heated and rolled into a finished product, and then hot-pressed and bonded to the surface of the current collector to obtain an electrode sheet.

[0043] In a specific embodiment of the present invention, during shear blending, the temperature is 30-90°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or any two thereof.

[0044] In a specific embodiment of the present invention, during the heating and calendering into sheets, the temperature may be 140-160° C. and the pressure may be 3-8 MPa.

[0045] In a specific embodiment of the present invention, the thickness of the heated calendered sheet is 20 to 120 μm, for example, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm or a range consisting of any two of them.

[0046] In a specific embodiment of the present invention, during the hot pressing bonding, the temperature may be 100 to 140° C. and the time may be 5 to 20 minutes.

[0047] In a specific embodiment of the present invention, the mass ratio of the dry binder, the electrode active material and the conductive agent is (1-10): (80-95): (5-10). The specific mass ratio of the dry binder, the electrode active material and the conductive agent is adjusted according to the composition requirements of the electrode sheet, but is not limited thereto.

[0048] In a specific embodiment of the present invention, the filler includes but is not limited to solid electrolyte particles, such as oxide solid electrolyte particles LLZO, sulfide solid electrolyte particles LGPS, etc. The specific amount of filler is adjusted according to the composition requirements of the electrode sheet, for example, it can be 1wt% to 5wt% of the total amount of materials (the mass of dry binder, electrode active material, conductive agent and filler), but is not limited thereto.

[0049] In a specific embodiment of the present invention, the electrode active material includes at least one of graphite, silicon-carbon material, silicon-oxygen material, lithium iron phosphate material and ternary positive electrode material; the conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon nanotubes, graphene and carbon nanofibers.

[0050] The current collector used in the present invention is conventionally selected according to the type of pole piece.

[0051] Examples 1 to 6 This embodiment provides a method for preparing a dry adhesive and an electrode sheet, comprising the following steps: (1) The grafted polymer is pre-dried at 120°C to remove water, then added to a twin-screw extruder and the screw is heated to a set temperature of 150°C to soften and melt the polymer.

[0052] (2) Adding the metal salt to the polymer obtained in step (1) through a hopper and kneading for 70 min, the screw speed during kneading is 120 rpm and the temperature is 150°C; then extruding through a co-extrusion die, cooling and drying, and then passing through a granulator to obtain a dry binder.

[0053] (3) Weigh the negative electrode active material graphite, the conductive agent carbon black, and the dry binder in a mass ratio of 92:5:3, add the graphite and carbon black into an extruder, stir and mix at 120 rpm for 10 min, then add the dry binder, stir and mix at 250 rpm for 10 min, and then stir and mix at 350 rpm / min for 30 min to obtain a fibrous solid.

[0054] (4) The fibrous solid obtained in step (3) is placed in a roller press and hot-rolled at 150°C / 5MPa to form a dry electrode film layer with a thickness of 20 to 120 μm (specifically 80 μm). The dry electrode film layer is then laminated to a negative electrode current collector (such as copper foil) and hot-rolled at 120°C for 10 minutes to obtain a dry negative electrode sheet.

[0055] The grafted polymer used in the preparation of the dry binder of Examples 1 to 6 is maleic anhydride grafted polypropylene (PP-MAH, weight average molecular weight of about 600000 Da) with a grafting rate of 1%, the metal salt is LiOH, the amount of PP-MAH and LiOH, and the grafted group unit MAH in PP-MAH and the cationic Li in LiOH are + The molar ratios are shown in Table 1.

[0056] Table 1 Information on the amount of raw materials used in different examples

[0057] Embodiments 7 to 11 Examples 7 to 11 refer to the preparation method of the dry binder and electrode sheet of Example 5, with the only difference being that PP-MAH is replaced with a mixture of PP-MAH with a grafting rate of 1% and maleic anhydride grafted polystyrene (PS-MAH, weight average molecular weight of about 600,000 Da) with a grafting rate of 1%. The specific amounts are shown in Table 2.

[0058] Table 2 Information on the amount of raw materials used in different examples

[0059] Embodiments 12 to 16 Examples 12 to 16 refer to the preparation method of the dry binder and electrode sheet of Example 10, with the only difference being: the type and amount of the metal salt are different. The specific information is shown in Table 3.

[0060] Table 3 Raw material dosage information of different examples

[0061] Comparative Example 1 Comparative Example 1 refers to the preparation method of Example 5, except that the grafted polymer is replaced by PTFE.

[0062] Experimental Example 1 The dry adhesives and pole pieces prepared in different embodiments and comparative examples were subjected to the following tests. The test results are shown in Table 4.

[0063] Room temperature ionic conductivity: The dry binders prepared in different embodiments and comparative examples were added to an internal mixer to soften to obtain a solid binder, which was then placed in a roller press and hot pressed at 5 MPa and 160°C to form a film. The film was then cut into discs (binder films) with a diameter of 17 mm and assembled with a stainless steel sheet into a sandwich battery clamp to test the room temperature (25°C) ionic conductivity of the binder. According to the formula , calculate the ionic conductivity at room temperature, where σis the ionic conductivity, l is the thickness of the adhesive film, S To test the contact surface area of ​​the adhesive film, R The intrinsic impedance of the adhesive film obtained by the impedance spectrum test.

[0064] Cohesive peel strength: The cohesive peel strength of the pole pieces prepared in different embodiments was tested with reference to GB / T 2792-2014 "Adhesive 180° Peel Strength Test Method"; specifically, the pole pieces were cut into test samples (length and width of 200mm×25mm), the metal side of the current collector was attached to a stainless steel plate with double-sided tape, 3M tape (Scotch 600 / 25mm wide) was attached to the coating surface, and the sample was rolled back and forth three times with a 1kg roller. In accordance with the national standard GB / T 2792-2014 test conditions, the cohesive force between the coating and the current collector was tested using a universal tensile machine.

[0065] Table 4 Test results of different embodiments

[0066] The room temperature ionic conductivity and cohesive strength of the PTFE binder in Comparative Example 1 are lower than those of the binder of the present invention with the same proportion, which indicates that the binder of the present invention has higher cost and performance advantages.

[0067] According to the test results of Examples 1 to 6, the room temperature ionic conductivity of the corresponding adhesive film has obvious differences at different LiOH contents. When the molar ratio of the grafted group unit in the grafted polymer to the cation in the metal salt (MAH:Li) is (0.5-2.6):1, the room temperature ionic conductivity of the corresponding adhesive film is significantly higher than that of the adhesive films with other ratios. The corresponding cohesive strength shows a trend of first increasing and then weakening with the increase of LiOH dosage, especially when MAH:Li is 1.3:1.

[0068] When different grafted polymers are mixed with LiOH, the type and proportion of the grafted polymers have an impact on the room temperature ionic conductivity of the binder film and the cohesive strength of the electrode. According to the test results of Examples 7 to 11, when the mass ratio of PP-MAH to PS-MAH is 9:1, the room temperature ionic conductivity of the binder and the cohesive strength of the electrode are the best, which is due to the unique microphase structure of the two-phase polymer after blending, which helps to improve the performance.

[0069] According to the test results of Example 10 and Examples 12 to 16, when LiOH is used as the metal salt, both better ionic conductivity and cohesive strength can be achieved.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a dry binder, characterized in that: The steps include: The grafted polymer and the metal salt are mixed and granulated to obtain a dry binder; The grafted polymer includes maleic anhydride grafted polypropylene.

2. The method for preparing a dry binder according to claim 1, characterized in that: The grafted polymers include maleic anhydride grafted polypropylene and maleic anhydride grafted polystyrene.

3. The method for preparing a dry binder according to claim 2, characterized in that: In the grafted polymer, the mass ratio of the maleic anhydride grafted polypropylene to the maleic anhydride grafted polystyrene is (80-98): (20-2).

4. The method for preparing a dry binder according to claim 1, characterized in that: Having at least one of the following characteristics: (1) In the grafted polymer, the proportion of the grafted group unit is 0.01wt% to 5wt%; (2) The metal salt is composed of cations and anions; the cations include Li + 、Na + , K + 、Zn 2+ 、Al 3+ Mg 2+ , Mn 2 + and Ga 2+ any one of; the anion includes any one of hydroxide, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, chloride, sulfate, carbonate, nitrate, perchlorate, tetrafluorophosphate, hexafluorophosphate, bis(oxalatoborate) and difluorooxalatoborate; (3) The metal salt includes at least one of LiOH, LiTFSI, LiFSI, LiClO4, LiBF4, LiPF6, LiBOB, LiDFOB, NaOH, NaClO4, NaPF6 and Na2CO3.

5. The method for preparing a dry binder according to claim 4, characterized in that: The molar ratio of the grafted group unit in the grafted polymer to the cation in the metal salt is (0.1-30):

1.

6. The method for preparing a dry binder according to claim 1, characterized in that: Firstly, the grafted polymer is melt-treated, and then mixed with the metal salt; The temperature of the melting treatment is 120-200°C, and the temperature of the mixing is 60-150°C.

7. A dry adhesive, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.

8. An electrode sheet, characterized in that: It is prepared by the dry binder prepared by the preparation method according to any one of claims 1 to 6 or the dry binder according to claim 7.

9. The method for preparing the electrode sheet according to claim 8, characterized in that: The steps include: (a) mixing a dry binder, an electrode active material, a conductive agent and optionally a filler in proportion, and blending by screw shearing to obtain a fiberized solid; (b) The solid material is heated and rolled into a sheet, and then hot-pressed and bonded to the surface of a current collector to obtain an electrode sheet.

10. The preparation method according to claim 9, characterized in that: The mass ratio of the dry binder, the electrode active material and the conductive agent is (1-10): (80-95): (5-10).

Citation Information

Patent Citations

  • Dry electrode binder and preparation method and application thereof

    CN117438531A

  • Modified binder and preparation method thereof, dry-method electrode plate and battery

    CN117691110A

  • Preparation process of PTFE (Polytetrafluoroethylene) suspension resin micropowder

    CN117777343A

  • Antistatic polypropylene material and preparation method thereof

    CN109181095A

  • Bondable resin composition

    JP1987227973A

Cited By

  • Dry binder, electrode for secondary battery comprising the same, secondary battery comprising the electrode, and method for preparing the binder

    KR103028223B1

  • Dry binder and preparation method therefor, and electrode sheet and preparation method therefor

    WO2026152635A1